Association between hyperuricemia and dietary retinol intake in Southwest China: a cross-sectional study based on CHNS database - Liang, Yi; Qiao, Tian; Ni, Xiaorong; Yang, Lihui; Yao, Tianhua; Liu, Yiya (Frontiers in Nutrition, 2025)
BackgroundHyperuricemia is increasingly common in Southwestern China and poses significant health risks, including gout and cardiovascular disease. Retinol intake has been hypothesized to affect uric acid levels, but this relationship remains unclear.MethodsData from 4,658 participants in the China Health and Nutrition Survey (CHNS) from 1991 to 2018 were analyzed. Dietary retinol intake was categorized using quantile-based methods, and hyperuricemia was identified as the primary outcome. Logistic regression models were used to estimate odds ratios and 95% confidence intervals, with analyses stratified by gender. Restricted cubic splines were utilized to evaluate the dose–response relationship.ResultsThe average age of participants was 40 ± 17.83 years, and 20.29% met the criteria for hyperuricemia. Logistic regression analysis identified a positive association between dietary retinol intake and hyperuricemia, with a more pronounced effect observed in men. The restricted cubic spline analysis revealed that the odds of hyperuricemia increased significantly when dietary retinol intake exceeded 3,538 IU/day for men and 4,504 IU/day for women.ConclusionHigh dietary retinol intake is associated with an increased risk of hyperuricemia, with a stronger association observed in males. These findings suggest that dietary retinol intake under recommendation levels might be necessary to prevent hyperuricemia-related adverse health outcomes.